2009
DOI: 10.1590/s1413-70542009000100001
|View full text |Cite
|
Sign up to set email alerts
|

Adubação com nitrogênio e boro na incidência de hastes ocas e na produção de couve-flor

Abstract: RESUMOO aparecimento de caule oco em couve-flor causa prejuízos aos produtores. O boro e o nitrogênio estão associados a essa desordem fisiológica, mas poucos estudos foram feitos em condições tropicais. Objetivou-se, no trabalho, avaliar os efeitos da adubação com N e B e da interação entre esses nutrientes na produção e na ocorrência de hastes ocas em couve-flor 'Shiromaru III', cultivada em solo da região de Ribeirão Preto (SP), durante o período de julho a setembro de 2003. O experimento foi conduzido em b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 14 publications
1
4
0
2
Order By: Relevance
“…The absorption of B did not follow the same patterns of the plant growth rate and high nitrogen concentration promoted reduction in B contents. Kojoi et al (2009) stated that K and S leaf contents in cauliflower were reduced with increasing boron doses, and the results of the present experiment behaved similarly, so that the V% with maximum TDM presented the leaf content of 139.39 mg kg -1 of B.…”
Section: Journal Of Agricultural Studiessupporting
confidence: 67%
“…The absorption of B did not follow the same patterns of the plant growth rate and high nitrogen concentration promoted reduction in B contents. Kojoi et al (2009) stated that K and S leaf contents in cauliflower were reduced with increasing boron doses, and the results of the present experiment behaved similarly, so that the V% with maximum TDM presented the leaf content of 139.39 mg kg -1 of B.…”
Section: Journal Of Agricultural Studiessupporting
confidence: 67%
“…The maximum values of curd fresh mass in response to N application in topdressing, 1,435 and 1,611 g, estimated with 331 and 307 kg ha -1 N for 'Snow Mystique' (Figure 2A), differ from the 1,294 g, estimated with 227 kg ha -1 N, 'Verona' (Oliveira et al, 2017); 1,301 g, estimated with 300 kg ha -1 N, 'Teresópolis Gigante' (Kano et al, 2010); and 901 g, estimated with 250 kg ha -1 N, 'Julia' (Camargo et al, 2008) for linear response; and without response to N, mean value of 791 g for 'Sharon' (Mello et al, 2009) and 1,730 g for 'Shiromaru III' (Kojoi et al, 2009). This shows the variation of the yield potential of cauliflower as a function of nitrogen fertilization.…”
Section: Resultsmentioning
confidence: 98%
“…In the field, N fertilization increases cauliflower yield (Camargo et al, 2008;Kano et al, 2010), but N shortage can result in low yield and curds of small size due to reduced leaf area (Torres et al, 2003). On the other hand, N fertilization does not influence cauliflower yield in intensely cultivated areas, often fertilized with nitrogen fertilizers (Kojoi et al, 2009;Mello et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Mello et al (2009) studying Sharon genotype with boron dose of 3 kg ha -¹ sowed directly in the pit or divided during the cycle verified that hollow stem was reduced more than 200% when compared with control without fertilization in both ways. Kojoi et al (2009) studying the effect of nitrogen fertilization (120, 180 and 240 kg ha -1 of N) and boron (2, 4 and 6 kg ha -1 of B) on the Shiromaru III genotype, showed that boron do not change presence or absent of hollow stem. They verified that hollow stem has linked direct with nitrogen fertilizations at high concentrations.…”
Section: Resultsmentioning
confidence: 98%